Drug utilization study of psychotropic drugs in psychiatry out-patient department of a tertiary care hospital in Kerala: a geriatric perspective - S. I. D, Shaikh Ubedulla; V., Niloofar (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Geriatrics tend to be the largest consumers of prescribed drugs exposing them to various drug interactions and adverse drug reactions. Present study is an attempt to assess the drug utilization pattern of psychotropic drugs among the geriatrics in psychiatry out-patient department (OPD) of a tertiary care hospital in Kerala. Methods: Prescriptions of patients diagnosed with psychiatric illness and being prescribed at least one psychotropic drug were collected. Prescriptions of male and female patients of age more than 60 years were sorted and analysed separately according to WHO core prescribing indicators. Results: 18% prescriptions were of geriatric population. Depressive disorders (38.89%) were the most common psychiatric disorder encountered. Out of 291 drugs prescribed in geriatrics, 237(81.44%) drugs were psychotropic drugs. Among the total psychotropic drugs prescribed, antipsychotics (39.24%) were the most commonly prescribed class of drugs. Average number of psychotropic drugs per prescription was 2.19, drugs prescribed by generic name were 2.06% and the drugs prescribed from NLEM (2015) were 41.77%. 86.11% of prescriptions contained more than one drug and 33.33% of prescriptions contained FDCs. Conclusions: Prescription analysis using WHO prescribing indicators showed some deviations from the standard which can be improved. A trend of polypharmacy was noted in this study. Prescribing using generic name and prescribing from NLEM was low as compared to the other reference studies. Proper strategies taken to overcome the inadequacies pointed out by this study can ensure the rational use of medicines.